A novel porous hollow carboxyl-polysulfone microsphere for selective removal of cationic dyes. (February 2022) - Zhang, Shangying; Dai, Fengna; Ke, Zhao; Wang, Qi; Chen, Chunhai; Qian, Guangtao; Yu, Youhai
Abstract: Herein, we obtained porous hollow carboxyl-polysulfone (PH-CPSF) microspheres through non-solvent-induced phase separation (NIPS) method and simple modification, used as highly efficient adsorbents for removing cationic dyes from sewage. The resulting PH-CPSF microspheres possess a hollow core and sponge-like shell structure, with high surface area, durable chemical inertness and structural stability. The as-synthesized PH-CPSF microspheres deliver a desirable adsorption effect after deprotonation treatment, with an adsorption capacity reaching up to 154.5 mg g −1 at 25 °C (pH = 7) of methylene blue (MB). The inter-molecular interactions between MB and the surface of the PH-CPSF, including π-π interaction, hydrogen bonding, strong charge attraction and weak charge attraction endow the adsorption ability of the PH-CPSF. The pseudo-second-order kinetic model pronounces in the adsorption behavior, and the adsorption equilibrium data is fitted to the Langmuir model. Moreover, PH-CPSF microspheres can also be used as adsorption fillers for large-scale water purification, and a removal rate of 94.0% for MB can be achieved under a flow rate of 8000 L m −3 h −1 . The reusability of 95.3% removal effect for PH-CPSF microspheres after 20 consecutive cycles can be attained by a simple regeneration treatment. The adsorption efficiency of the PH-CPSF microspheres was evaluated by variety of cationic and anionic dyes, with high adsorption capacity toward cationic dyes (100%) and less than 10% toward anionic dyes. These results manifest that PH-CPSF microspheres are a potential adsorbent with long-term purification capabilities, which are expected to be used in small and large-scale sewage treatment. Graphical abstract: Image 1 Highlights: Carboxyl polysulfone (PH-CPSF) microspheres were prepared by the non-solvent-induced phase separation and click reaction. The as-obtained PH-CPSF possess honeycomb core-shell and porous hollow structure with abundant functional groups. Highly selective cationic dyes remove efficiency, mechanical/chemical stability and reusability are achieved by PH-CPSF. The functional PH-CPSF show its potential for large-scaled sewage purification.